2018
DOI: 10.1111/papt.12194
|View full text |Cite
|
Sign up to set email alerts
|

Is mentalization‐based therapy effective in treating the symptoms of borderline personality disorder? A systematic review

Abstract: Mentalization-based therapy (MBT) is increasingly being considered as a treatment for people with borderline personality disorder (BPD), and a systematic review was required to investigate its effectiveness. MBT was found to be equally as effective or superior to well-established comparison treatments of BPD, however, the majority of studies was of unsatisfying quality. Little is known about the mechanisms of MBT. Further, better quality trials are needed to investigate its efficacy in treating BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 76 publications
2
36
0
1
Order By: Relevance
“…A systematic review of 75 randomized clinical trials testing psychotherapy for BPD [ 163 ] identified 16 approaches to treatment, with Dialectical Behavior Therapy [ 105 , 106 ] and Mentalization-Based Therapy (MBT) [ 185 ] most often the focus. Overall, despite evidence of larger reductions in BPD symptom severity by active psychotherapies than treatment as usual, the average reduction of 3.6 points on a 0–36 scale was only slightly higher than the threshold for a minimal clinically relevant difference (MIREDIF; 3.0 points).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of 75 randomized clinical trials testing psychotherapy for BPD [ 163 ] identified 16 approaches to treatment, with Dialectical Behavior Therapy [ 105 , 106 ] and Mentalization-Based Therapy (MBT) [ 185 ] most often the focus. Overall, despite evidence of larger reductions in BPD symptom severity by active psychotherapies than treatment as usual, the average reduction of 3.6 points on a 0–36 scale was only slightly higher than the threshold for a minimal clinically relevant difference (MIREDIF; 3.0 points).…”
Section: Main Textmentioning
confidence: 99%
“…A detailed analysis of outcomes of a randomized clinical effectiveness study showed that DBT resulted in greater reductions in experiential avoidance and expressed anger than community-based expert treatment, but not for guilt, shame, anxiety or anger suppression and dyscontrol [ 125 ]. Controlled evaluations of MBT also have not shown evidence of its superiority compared to treatment as usual or supportive psychotherapy in the domains of anxiety, depression, social adjustment, and relational functioning [ 185 ]. These symptoms are quite similar to the symptoms of PTSD and cPTSD, which suggests that even the BPD psychotherapies with the strongest empirical support may be enhanced by the addition of therapeutic modalities that directly target the symptoms of PTSD and cPTSD /DSO.…”
Section: Main Textmentioning
confidence: 99%
“…According to the theory underlying MBT, the core pathology underpinning BPD is a vulnerability to shift to nonmentalizing modes in states of emotional arousal, and MBT offers therapeutic interventions to help the patient regain adequate mentalizing and facilitate proper affect regulation (Bateman & Fonagy, ). Two recent reviews concluded that although more high‐quality studies are needed, the current evidence indicates that MBT is a potentially effective treatment for BPD in adults (Malda‐Castillo, Browne, & Perez‐Algorta, ; Vogt & Norman, ). With respect to early intervention, mentalization‐based approaches have been conducted for both adolescents with and without BPD features (Laurenssen et al, ; Rossouw & Fonagy, ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating personality factors bears high importance for understanding all psychological components of tinnitus-related distress and its maintenance, as personality may affect both exposure and reactivity to stressful events as well as differential choices of coping efforts and their differential effectiveness (Bolger and Zuckerman, 1995). Moreover, success rates of treatment approaches such as schema (Jacob and Arntz, 2013) or mentalizationbased therapy (Vogt and Norman, 2018) increasingly refute the notion that personality-associated persistent emotional difficulties are stable. These treatments offer promising tools to address personality factors as modifiable treatment targets.…”
Section: Introductionmentioning
confidence: 99%